The Effect of Marketing Knowledge Management on Innovation Performance and Business Performance - Widyana Widyana; Yanti Mayasari Ginting (Program Pascasarjana STIE Amkop Makassar, 2022)
The role of marketing knowledge management can shape the company's dynamic capability to sustainably survive and create valuable innovations. This study aims to determine the effect of Marketing Knowledge Management on Innovation Performance and Business Performance. The research was conducted at PT. Decormart Mitra Jaya Pekanbaru. The population in this study were all employees of PT Decormart Mitra Jaya as many as 57 employees. The sampling technique used in this study is saturation sampling, that is all members of the population are used as samples. The data analysis technique used for hypothesis testing is path analysis with the Partial Least Square (PLS) approach using the SmartPLS ver 3.0 M3 software application. The results of this study indicate that Marketing Knowledge Management has a positive and significant effect on Innovation Performance, Marketing Knowledge Management has a positive and significant effect on Business Performance, Innovation Performance has a positive and significant effect on Business Performance, and Marketing Knowledge Management has a significant effect on Business Performance mediated by Innovation Performance.